Anthropogenic noise impairs owl hunting behavior. (July 2016) - Mason, J. Tate; McClure, Christopher J.W.; Barber, Jesse R.
Abstract: Emerging evidence indicates that anthropogenic noise has highly detrimental impacts on natural communities; however, the effects of noise on acoustically specialized predators has received less attention. We demonstrate experimentally that natural gas compressor station noise impairs the hunting behavior of northern saw-whet owls ( Aegolius acadius ). We presented 31 wild-caught owls with prey inside a field-placed flight tent under acoustic conditions found 50–800 m (46–73 dBA) from a compressor station. To assess how noise affected hunting, we postulated two hypotheses. First, hunting deficits might increase with increasing noise—the dose–response hypothesis. Secondly, the noise levels used in this experiment might equally impair hunting, or produce no impact—the threshold hypothesis. Using a model selection framework, we tested these hypotheses for multiple dependent variables—including overall hunting success and each step in the attack sequence (prey detection, strike, and capture). The dose–response hypothesis was supported for overall hunting success, prey detection, and strike behavior. For each decibel increase in noise, the odds of hunting success decreased by 8% (CI 4.5%–11.0%). The odds of prey detection and strike behavior also decreased with increasing noise, falling 11% (CI 7%–16%) and 5% (CI 5%–6%), respectively. These results suggest that unmitigated noise has the potential to decrease habitat suitability for acoustically specialized predators, impacts that can reverberate through ecosystems. Highlights: Northern saw-whet owls hunted under noise levels corresponding with distances of 50 - 800 m from a compressor station For each dB increase in noise, the odds of an owl successfully capturing prey declined by 8%. For acoustically specialized predators, noise should be managed by dose of the pollutant.